2019
DOI: 10.3390/cells8010028
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the TRPM2 Channel Expression in Human Neuroblastoma SH-SY5Y Cells Augments the Susceptibility to ROS-Induced Cell Death

Abstract: Human neuroblastoma SH-SY5Y cells are a widely-used human neuronal cell model in the study of neurodegeneration. A recent study shows that, 1-methyl-4-phenylpyridine ion (MPP), which selectively causes dopaminergic neuronal death leading to Parkinson’s disease-like symptoms, can reduce SH-SY5Y cell viability by inducing H2O2 generation and subsequent TRPM2 channel activation. MPP-induced cell death is enhanced by increasing the TRPM2 expression. By contrast, increasing the TRPM2 expression has also been report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…2. Accumulating evidence indicates that SH-SY5Y cell has a PARP-1 activation 28,30 . The PARP-1 expression, TRPM2 mRNA expression, IL-1β and TNF-α release levels were higher in the SH-SY5Y as compared to the control and RSV (p ≤ 0.001).…”
Section: Hypx-induced Fluorescence Intensity Of Free Zinc Ion (Zn2 + mentioning
confidence: 99%
“…2. Accumulating evidence indicates that SH-SY5Y cell has a PARP-1 activation 28,30 . The PARP-1 expression, TRPM2 mRNA expression, IL-1β and TNF-α release levels were higher in the SH-SY5Y as compared to the control and RSV (p ≤ 0.001).…”
Section: Hypx-induced Fluorescence Intensity Of Free Zinc Ion (Zn2 + mentioning
confidence: 99%
“…As discussed above, the activity of nuclear PARP, particularly PARP-1, is crucial for the induction of ADPR generation and subsequent TRPM2 channel activation by ROS and other OS-inducing pathological stimuli. PARP inhibitors have been used in many studies as an alternative or additional means to prevent OS-induced TRPM2-mediated effects [ 36 , 39 , 48 , 74 , 75 , 82 , [121] , [122] , [123] , [124] , [125] , [126] ], including cell death. Example PARP inhibitors include SB-750139, N-(6-oxo-5,6-dihydro-phenanthridin-2-yl)-N,N-dimethylacetamide (PJ34), 3-aminobenzamide (3-AB) and 3,4-dihydro-5-[4-(1-piperidinyl)butoxy]-1(2H)-isoquinolinone (DPQ).…”
Section: Trpm2 Channel Properties Activation Mechanisms and Pharmacmentioning
confidence: 99%
“…Both MPP + -induced cell death and activation of the apoptotic pathways were also inhibited by treatment with TRPM2-siRNA [ 44 ]. In a more recent study using PI staining, we have shown that exposure to H 2 O 2 (100–500 μM for 24 h) induced concentration-dependent cell death in SH-SY5Y cells and that H 2 O 2 -induced cell death was suppressed or abolished by treatment with 2-APB, PJ34 or DPQ [ 123 ]. Furthermore, by generating a stable SH-SY5Y cell line overexpressing the TRPM2 channel and comparing cell death following exposure to H 2 O 2 (30–300 μM for 24 h), we further demonstrated that an increase in TRPM2 channel expression remarkably enhanced susceptibility to H 2 O 2 -induced cell death [ 123 ].…”
Section: Trpm2 In Neuronal Cell Death Associated With Ischemia/reperfmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the data in cancer models mostly supports the conclusion that TRPM2 expression and function have an important role in preserving cancer cell viability and survival. Consistent with this view, the TRPM2 channel has been found to be highly expressed in numerous cancers including bladder, breast, head and neck, lung, pancreatic, prostate, melanoma, and neuroblastoma [ 51 ], among which most studies were focused on the neuroblastoma [ 58 , 59 , 60 , 61 , 62 , 63 , 64 ] ( Figure 2 ). The higher levels of ROS in cancer cells impel the enhancement of their anti-oxidant capacity to detoxify ROS and preserve cells viability.…”
Section: Transient Receptor Potential Melastatin 2 (Trpm2) Channelmentioning
confidence: 60%